Unmasking the state of risk management in Zimbabwe’s Gweru urban secondary schools - Dzimiri, Wonderful; Chinyauro, Munyaradzi (GLOBEEDU Group, 2016)
Incidents of robberies, fraud, fire accidents, natural disasters, thefts and burglaries in educational institutions are a common feature in press reports. Interrogation of risk management conceptualization, provisions and mechanisms in schools becomes of particular interest. In this study, we argue that schools continue to do business as usual in the absence of policies, mechanisms and practices hinged on management of risk. The study focused on participants’ conceptualization of risk management, provisions and mechanisms in place, and challenges faced. The study of seven secondary schools in the Gweru Urban district, involved School Development Committee/Association chairpersons, school heads and deputy heads, and an official from provincial education office, all purposively selected as information- rich participants by virtue of positions they occupied. Informed by the post-positivist mixed methods paradigm, interview, questionnaire and observation methods were used to collect both quantitative and qualitative data. Analysis of quantitative data employed descriptive statistics (numbers [N] and corresponding Percentages [%]), while qualitative data were analysed using a thematic approach identifying patterns that emerged from the data, and enriched quantitative evidence. Findings indicated that schools were generally not risk-prepared. Evidence showed a poor, uninformed conceptualisation of risk management, which consequently did not appear as a priority during planning; there was general lack of awareness of potential risk areas in the schools coupled with a lack of policies and installation of mechanisms geared at managing risk, which, in some cases, placed lives of stakeholders at risk. The state of risk management in schools studied calls for deliberate preparation of risk management manuals and training efforts for school management personnel and parent members of the SDC/SDA structures. Such efforts could focus on risk management in terms of safety, emergency procedures, financial procedures, security of premises, and assets.